The role of academic ability indicators in big-fish-little-pond effect research: A comparison study. Issue 4 (4th July 2018) - Vogl, Katharina; Schmidt, Isabelle; Preckel, Franzis
ABSTRACT: The authors examined the big-fish-little-pond effect (BFLPE) on academic self-concept (ASC) using different indicators of academic ability (i.e., achievement test, cognitive ability test, grades corrected for grading-on-a-curve effects, uncorrected grades). They investigated under what circumstances grades are suitable indicators of academic ability in BFLPE research. The sample comprised 730 sixth-grade students from 30 classes belonging to the top track of the German secondary high school system. Using multilevel models, all indicators of academic ability exhibited negative contrast effects on ASC at class level (i.e., BFLPE). The authors found the strongest effects for corrected grades, followed by achievement tests, cognitive ability, and, finally, uncorrected grades. Thus, the study provides evidence for the usage of grades within BFLPE research for investigating the BFLPE.